Mirror visual feedback as therapeutic modality in unilateral upper extremity complex regional pain syndrome type I: randomized controlled trial - Machač, Stanislav; Chasáková, Ludmila; Kakawand, Soroush; Kozák, Jiří; Štěpánek, Lubomír; Vejvalka, Jan; Kolář, Pavel; Černý, Rudolf (European journal of physical and rehabilitation medicine, 2024)
BACKGROUND: There is growing evidence for the effectiveness of mirror therapy (MT) on pain reduction in patients with type I complex regional pain syndrome (CRPS I). AIM: To evaluate the efficacy of MT on pain reduction and hand function in subjects with unilateral upper extremity CRPS I. DESIGN: Randomized controlled trial with control group cross-over (half cross-over design). SETTING: Subjects with CRPS I were outpatients of a university hospital and cooperating centers. All patients carried out the daily exercise at home. POPULATION: Subjects with unilateral upper extremity CRPS I meeting the Budapest diagnostic criteria. METHODS: Subjects were randomly divided into two groups. Group A (N.=13) carried out a ten-minute MT exercise daily, for a total duration of six weeks. Group B (N.=14) acted as a control group for six weeks followed by six weeks of MT with the same characteristics as Group A. Upper extremity active range of motion, strength, dexterity, limb volume, affected-to-unaffected hand temperature difference, and health-related quality of life were evaluated before and after each period. Daily records on the visual analogue scale were used for pain evaluation. Effectiveness was calculated using mixed-effects modelling for between-group comparisons and within-group variability, and identification of significant predictors. RESULTS: Twenty-three females and four males with an average age of 56.1±9.6 years completed the study. Except for the affected-to-unaffected hand temperature difference, both groups consistently demonstrated significant or near-significant improvements in measured parameters after MT period. The improvements were evident upon an intergroup comparison of Group A and the control period of Group B as well as longitudinally within Group B. No significant improvement was found during the control period. CONCLUSIONS: Principles focused on mirror visual feedback to the central nervous system can sustain promising therapeutic potential as part of the treatment for pain reduction and hand function in CRPS I patients. CLINICAL REHABILITATION IMPACT: MT can be considered as part of the therapeutic regimen employed for the treatment of CRPS I.
Keywords: bolest; Pain; Humans; lidé středního věku; Quality of Life; Sudeckův syndrom; senzorická zpětná vazba; komplexní regionální syndromy bolesti; Female; Aged; výsledek terapie; senioři; lidé; Feedback, Sensory; kvalita života; horní končetina; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Upper Extremity; Complex Regional Pain Syndromes; Reflex Sympathetic Dystrophy; mužské pohlaví